HOTS-based language assessment literacy: Challenges and prospects in English language teaching - Sumardi Sumardi; Rizki Indra Guci (Universitas Pendidikan Indonesia, 2023)
The issues of inaccurate and invalid language assessment were mainly due to teachers’ lower level of assessment literacy and teachers' inadequate skills to design higher-order thinking skills (henceforth HOTS) based language assessments. Thus, this paper aims to mainly portray teachers’ HOTS-based language assessment literacy in English language teaching (ELT) classrooms after they participated in training on HOTS-based language assessment. A case study was employed, and forty-three ELT teachers from secondary schools voluntarily participated in the current study. Some of them were interviewed, and the test items they constructed were analyzed to examine if their HOTS-based language assessment literacy was reflected in the quality of the test items. The findings showed that ELT teachers who engaged in training gained the basic level of knowledge and comprehension of HOTS-based language assessment. However, their knowledge and comprehension are not parallel with their skills in constructing HOTS-based test items. The paper ends with recommendations for the stakeholders (school principals, educational authorities, and training providers) responsible for designing future training programs to enhance ELT teachers' language assessment literacy.